1979
DOI: 10.1088/0022-3727/12/5/020
|View full text |Cite
|
Sign up to set email alerts
|

Avalanche breakdown in n-hexane

Abstract: Time lags to breakdown in n-hexane have been measured in high over-voltages, using approximately 100 ns width rectangular pulses. At a constant field, the time lags are divided into two types, N and B, at a 'critical distance' d. Above dc, Laue plots have almost similar kinked-line characteristics; below dc, a straight line is obtained. From the prebreakdown current estimated from the voltage waveforms, the ionisation coefficient, which increases with increasing applied fields, is estimated to be 6.4*103 cm-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The breakdown process normally takes several microseconds in these models. However, a micro-EDM RC pulse discharge generally takes only hundreds of nanoseconds and the expansion velocity of the discharge channel is 10 4~1 0 5 m/s in the liquid [20,21]. Therefore, the expansion mechanism simply based on the bubble dynamics is insufficient to explain the rapid discharge in micro-EDM.…”
Section: Plasma Breakdown Stagementioning
confidence: 99%
See 1 more Smart Citation
“…The breakdown process normally takes several microseconds in these models. However, a micro-EDM RC pulse discharge generally takes only hundreds of nanoseconds and the expansion velocity of the discharge channel is 10 4~1 0 5 m/s in the liquid [20,21]. Therefore, the expansion mechanism simply based on the bubble dynamics is insufficient to explain the rapid discharge in micro-EDM.…”
Section: Plasma Breakdown Stagementioning
confidence: 99%
“…Due to its complex composition, it is difficult to determine the thermal and physical properties of kerosene. Therefore, alkanes that are the main composition of the kerosene are selected to replace kerosene in the calculation [21]. Discharge parameters used in the calculation are 10000pF discharge capacity, 1μm discharge gap, and 60V discharge voltage.…”
Section: The Calculation Of Plasma Modelmentioning
confidence: 99%
“…As well known, two kinds of initiation mechanism of streamer discharges in dielectric liquids have been proposed, so called bubble process and electronic process [10]. If the electronic process is a dominant factor of the streamer initiation, the initiation probability per unit time is kept constant at any time because the process is based on the stochastic mechanism such as avalanche breakdown [17]. If the bubble process is a dominant factor for the streamer initiation, the streamer discharge takes place after the physical processes for the formation of micro bubbles produced by Joule heating due to current concentration near the point electrode, so that the plot of the initiation time lag is kept flat at the initial stage of the voltage application.…”
Section: Initiation Processmentioning
confidence: 99%
“…The dielectric properties of LNG are difficult to be obtained through conventional high-voltage (HV) tests . Fortunately, n -hexane is a hydrocarbon whose electrical properties are well studied and has some similarities to the molecules that make up LNG. , In addition, n -hexane electrical test and simulation research are in good agreement . Moreover, some calculated values showed that the breakdown field strength of liquid methane (LCH 4 ) is much lower than that of other cryogenic liquids, so LNG (methane as the main component) seems to be unsuitable as an insulating medium .…”
Section: Introductionmentioning
confidence: 99%